EMPOWERING INDONESIAN MUSLIM WOMEN WITH ISLAMIC LITERACY: A PERSPECTIVE ON ADULT EDUCATION THEORIES - Bulqia Mas'ud (IQRA : JURNAL MAGISTER PENDIDIKAN ISLAM, 2021)
Abstract: The issue of women empowerment in Indonesia has gotten a lot of attention since women are thought to be very prone to social disadvantages. This paper discusses women empowerment for Indonesian Muslim with Islamic literacy and education for social change analyzed by adult education theories. After studying some literatures, the writer is able to elaborate the concept of adult education, how adult education with Islamic literacy could empower Muslim women, the dilemma emerging from the concept of empowerment in Islamic education in the study case. In addition, the paper also investigates the possibilities of women empowerment through Islamic education for social change. After the issues are discoursed, this paper concludes that adult education with Islamic literacy contributes to their self-development and self-actualisation which empower Muslim women intellectually and professionally which give Muslim women comprehensive knowledge as an individual and as a part of society. Besides, the adult education with Islamic literacy also works in social transformation through dissemination of Islamic knowledge within the society. Since Muslim women have the biggest number in Indonesia, it is very important to propose the professional Islamic education for Muslim women as the ultimate solution to overcome Muslim women’s problems in Indonesia.